Surface nanocrystallization of body-centered cubic beta phase in Ti–6Al–4V alloy subjected to ultrasonic surface rolling process - Ao, Ni; Liu, Daoxin; Zhang, Xiaohua; Liu, Chengsong; Yang, Jing; Liu, Dan (Surface & coatings technology, 2019)
The nanocrystallization mechanism of a body-centered cubic β phase in Ti–6Al–4V alloy subjected to ultrasonic surface rolling process was investigated. A gradient nanostructure (thickness: ~400 μm) that the β grain size in thickness gradually changes from ~0.76 μm in the interior to ~36.5 nm at the topmost surface was formed in Ti–6Al–4V alloy surface layer. The gradient nanostructure of the β phase is formed primarily via dislocation activities without the occurrence of deformation twinning. Dislocations were first generated in β phase at the phase boundaries where a high density of dislocations occurred in α phase. The coarse β grains were then gradually transformed into equiaxed nano grains via longitudinal splitting and transverse breakdown, which are induced by dislocation glide, entanglement, accumulation, and rearrangement. Additionally, with increasing strain, the β nanograins will be further refined via dislocation activities. •The softer β phase deforms after α phase in USRP-treated Ti–6Al–4V alloy.•β phase deforms mainly via dislocation motion without twinning occurring.•Dislocations in β phase initiate at the α/β phase boundaries.•There is no shear band observed during deformation.